The Effectiveness of the Tikrar Method in Enhancing Quranic Memorization among Elementary School Students - Pebrianto Pebrianto; Nurhayati Nurhayati; Zulmasri Zulmasri (STIT Ahlussunnah Bukittinggi, 2026)
The low level of Quranic memorization ability among elementary school students remains a challenge in Islamic education. This condition is reflected in students' lack of fluency in memorization, inaccuracies in the application of tajwid and makhraj, and difficulties in retaining previously memorized verses. This study aimed to examine the effectiveness of the Tikrar method in improving the Quranic memorization ability of elementary school students. The study employed a quantitative approach using a quasi-experimental design through the administration of pretests and posttests. The population consisted of 39 students, while 11 students were selected as the research sample using purposive sampling. Data were collected through Quranic memorization tests, observations, and documentation. Students' memorization ability was assessed based on fluency, accuracy of tajwid, accuracy of makhraj, accuracy in recalling verses, and self-confidence. The data were analyzed using descriptive statistical techniques to compare students' performance before and after the treatment. The findings revealed an improvement in students' Quranic memorization ability following the implementation of the Tikrar method. Improvements were observed in memorization fluency, reading accuracy, and students' confidence in reciting their memorized verses. Furthermore, observational data indicated that students became more active, focused, and enthusiastic during the memorization learning process. These findings suggest that the Tikrar method has the potential to serve as an effective instructional strategy for enhancing elementary school students' Quranic memorization ability through a systematic and continuous repetition process.